Covid-19 emergency management and preparedness in cross-border territories. Collection of experiences, needs and public health strategies in the framework of interreg GESTI.S.CO. project - Brambilla, Andrea; Mosca, Erica Isa; Isabella, Arianna; Bignami, Daniele Fabrizio; Buffoli, Maddalena; Gola, Marco; Mangili, Silvia; Bertulessi, Manuel; Zambrini, Federica; Pogliani, Arianna; Boschini, Ilaria; Callari, Luca; et al. (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: The Covid-19 pandemic highlighted management difficulties in neighboring territories. The aim of the paper is to report the needs of different stakeholders during, before and after Covid-19 emergency with specific regard to challenges faced by public administrators in confined territories. Methods: In the framework of Interreg GESTI.S.CO. project the study has been designed with two methodological steps: i) a co-design workshop and ii) a web-based survey. The workshop includes both an audience interaction session and focus groups. Then, starting from the focus group results, the survey has been designed with 30 questions and submitted to the 227 municipalities located between Italy and Switzerland to understand the implementation of Public Health strategies in local emergency planning. Results: The interactive session highlighted that most of the critical issues are related to the lack of communication and planning in Public Health policies. The survey highlighted that the local emergency plans rarely integrate a section on health emergencies (30% Italy and 50% Switzerland). Only 20% of the respondents dedicated a section for Covid-19 emergency management. Most of them did not activate initiatives to support mental health. 90% of the municipalities did not cooperate with the neighboring country, but half of them think that it would have been much more useful. The 55% of the Italian respondents are currently updating their emergency plan and will implement it with some Public Health input. Conclusions: The study provides insights that can support policy makers in improving their strategy in responding to future pandemic. (www.actabiomedica.it)